2013
DOI: 10.18632/oncotarget.1561
|View full text |Cite
|
Sign up to set email alerts
|

Frequent amplification of ORAOV1 gene in esophageal squamous cell cancer promotes an aggressive phenotype via proline metabolism and ROS production

Abstract: Chromosomal band 11q13 seems to be one of the most frequently amplified lesions in human cancer, including esophageal squamous cell cancer (ESCC). The oral cancer overexpressed 1 (ORAOV1) gene has been identified within this region, but its detailed biological function in human ESCC remains largely unclear. In our clinical samples of stage III ESCC, ORAOV1 amplification was observed in 49 of 94 cases (53%). ORAOV1 amplification was significantly associated with a poorly differentiated histology and tumors loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 24 publications
0
59
0
Order By: Relevance
“…7 These include oncogenes, such as CPT1A , ANO1 , ORAOV1 , CCND1 , FGF3, FGF4, FGF19 , CTTN , and MIR548K ; their contributions to the malignant phenotype of ESCC cells have been verified. 811 The genomic material between 11q13.2 and 11q13.3 is nonuniformly increased, with the most recurrent peak spanning CCND1. 12 …”
Section: Somatic Alterations In Escc Genomesmentioning
confidence: 99%
“…7 These include oncogenes, such as CPT1A , ANO1 , ORAOV1 , CCND1 , FGF3, FGF4, FGF19 , CTTN , and MIR548K ; their contributions to the malignant phenotype of ESCC cells have been verified. 811 The genomic material between 11q13.2 and 11q13.3 is nonuniformly increased, with the most recurrent peak spanning CCND1. 12 …”
Section: Somatic Alterations In Escc Genomesmentioning
confidence: 99%
“…Togashi et al (7) also reported that oral cancer overexpressed 1 (ORAOV1) located at 11q13 was amplified in 53% of ESCC patients, and its amplification was significantly associated with poor differention status. Overexpression of ORAOV1 could enhance tumorigenicity and tumor growth (7). Thus, the identification of candidate tumor-associated genes is crucial in revealing the mechanism of tumorigenesis of esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Pycr1 may serve its protective role from oxidative stress and apoptosis possibly through binding with other proteins, such as DJ-1 and ribonucleotide reductase small subunit B [29,31]. Although we did not observed changes in proline levels, other factors such as proline oxidase [32] may be involved. Regardless, the changes reported herein for Pycr1 are novel and the higher Pycr1 levels in FVB/N pancreata correlate with the lower observed caspase-3 activation that we observed.…”
Section: Discussionmentioning
confidence: 75%